Superhalogen Anions Supported by the Systems Comprising Alternately Aligned Boron and Nitrogen Central Atoms - Cyraniak, Adrianna; Faron, Dawid; Freza, Sylwia; Anusiewicz, Iwona; Skurski, Piotr (Frontiers in Chemistry, 2022)
Using DFT/B3LYP and OVGF electronic structure methods with flexible atomic orbital basis sets, we examined the series of polynuclear superhalogen anions matching the (BF3(BN)nF4n+1)– formula (for n=1 10,13,18 20) containing alternately aligned boron and nitrogen central atoms decorated with fluorine ligands. It was found that the equilibrium structures of these anions correspond to fully extended chains (with each B and N central atom surrounded by four substituents arranged in a tetrahedral manner) and thus mimic the globally stable fully extended (all trans) conformations of higher n alkanes. The vertical electron detachment energies of the (BF3(BN)nF4n+1)– anions were found to exceed 8 eV in all cases and gradually increase with the increasing number of n. The approximate limiting value of vertical electron binding energy that could be achieved for such polynuclear superhalogen anions was estimated as equal to ca. 10.7 eV.